Um estudo de caso da rede de atenção psicossocial de São Carlos - Wolff, Laura Chiaramonti (Universidade Federal de São Carlos, 2022)
The Psychiatric Reform in Brazil conquers for mental health care the implementation of a psychosocial care model, to the detriment of the asylum model, through public mental health policies and the consolidation of the Psychosocial Care Network (RAPS). However, despite the regulations, the replacement of models is not immediate and the full reproduction of psychosocial practices is not yet a reality. Therefore, the present study was proposed under a qualitative approach, of an empirical and theoretical character, with the objective of investigating and understanding the constituent elements of the Municipal Mental Health Policy of São Carlos and how it guides the work in the local network. To this end, the production of data took place through remote interviews with 7 managers of the local health system and document analysis of ordinance nº3.088/2011. The interviews underwent a thematic content analysis, just as the document underwent its thematic content analysis. Subsequently, the results of the analyzes were articulated in the discussion. As main results, the thematic analysis of the interviews generated 2 categories of meaning: i) the mental health policy in the macro context, in which the constitutive elements of the municipal mental health policy were identified through the gaps in the organizational and functional proposal of the policy; ii) the mental health policy in the micro context, in which managers' understanding of the local RAPS was identified. The thematic analysis of the ordinance generated just one category: psychosocial care model, in which the main aspects of the national mental health policy were apprehended. Articulating the analyses, it is concluded that there is a gap between the Mental Health policy of the municipality of São Carlos and Ordinance nº 3.088/2011, especially in the composition of services, articulation between services and sectors, effective matrix support and health care mental health in primary care (all elements provided for in Ordinance number. 3088/2011). In addition, it is also concluded that the managers' understanding of the municipality's mental health policy focused on the absence of a document such as an ordinance or a technical note that formalized a flow of referrals.
A case study of the psychosocial care network of São Carlos
Keywords: Rede de Atenção Psicossocial; Política de Saúde Mental; Reforma Psiquiátrica; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL